APPLICATION OF ARGUMENT MAPPING METHODS TOWARD CRITICAL THINKING SKILLS OF SENIOR HIGH SCHOOL STUDENTS - siti mulya agnah (Biodidaktika : Jurnal Biologi dan Pembelajarannya, 2018)
This study aims to determine the results of critical thinking skills of high school students by applying the method of argument map on the material Circulatory System. The method used in this research is quasi experiment with Static Group Pretest-Posttest Design design through procurement of control class. The study population is XI MIPA SMAN 97 Jakarta with the sample of research as many as two classes, namely XI MIPA 1 and 3 which contains each of 36 students. The instrument used in this research is a description test. Based on data analysis of research results, the average value of pretest and posttest obtained in the control class of 28.89, while in the experimental class obtained at 25.08 and posttest of 38.67. The result of t-test of pretest and posttest of control class is obtained tcount (0,000) <ttabel (2,306) which is not significantly different, whereas in t-test result pretest and posttest of experiment class with tcount (25,528)> ttable (2,306) differ significantly. The test was continued with N-Gain calculation, where the control class obtained N-Gain of 0.4 and the experimental class obtained N-gain of 0.7. The N-Gain score criteria in the control class include the medium category and the experimental class included in the high category. From the results of this study can be concluded that the application of argument map method on the circulatory system material can improve the critical thinking ability of learners.